2017
DOI: 10.1097/coc.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and Functional Hazards of Obesity Among Patients With Locally Advanced Rectal Cancer Following Neoadjuvant Chemoradiation Therapy

Abstract: Objective Obesity is a major health concern and risk factor for colorectal cancer that may also impact cancer treatment and outcomes. Rectal cancer response to chemoradiotherapy (CXRT) is associated with long-term survival and sphincter preservation. The purpose of this study was to evaluate the impact of obesity on treatment outcomes after neoadjuvant CXRT for rectal cancer. Methods A retrospective cohort study of patients diagnosed (1993–2010) with cT3-4 or cN+ (by EUS, CT, or MRI) rectal carcinoma and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Previous studies have reported that the obesity affects the response to NACT in various solid tumors such as prostate cancer, rectal cancer, breast cancer, and pancreas cancer (Farr et al, 2017;Park et al, 2017;Duconseil et al, 2019;Sun et al, 2020). Park et al, (2017) reported that obesity reduced the complete response rate by 40% in their study with rectal cancer patients receiving neoadjuvant CRT. Likewise, another study of pancreatic cancer by Duconseil et al, (2019) has reported that obesity is determined as the factor affecting survival.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that the obesity affects the response to NACT in various solid tumors such as prostate cancer, rectal cancer, breast cancer, and pancreas cancer (Farr et al, 2017;Park et al, 2017;Duconseil et al, 2019;Sun et al, 2020). Park et al, (2017) reported that obesity reduced the complete response rate by 40% in their study with rectal cancer patients receiving neoadjuvant CRT. Likewise, another study of pancreatic cancer by Duconseil et al, (2019) has reported that obesity is determined as the factor affecting survival.…”
Section: Discussionmentioning
confidence: 95%
“…Also, obesity may decrease the possibility of sphincter preservation [89]. In addition, some studies reported a relationship between obesity and oncologic outcomes of patients with rectal cancer following nCRT, although their results were controversial [1011121314]. Given the fact that obesity is associated with inflammation and angiogenesis [15] and is associated with the chronic oxidative stress [16], it is possible to consider the possibility that obesity is related to the response of radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, this observation only occurred in the bystander cells treated with TCM from irradiated rectal cancer biopsies, perhaps suggesting that obesity status may influence the behaviour of bystander cells following radiation. This is an interesting and clinically relevant result as it has been reported that overweight and obese patients have poorer responses to neoadjuvant treatment and worse outcomes in rectal cancer [ [20] , [21] , [22] ]. Moreover, when we correlated levels of metabolites in the secretome of mock-irradiated rectal cancer tissue we found significant correlations between VFA and leucine and ethanol.…”
Section: Discussionmentioning
confidence: 72%
“…It has been reported that overweight or obese rectal cancer patients have a poorer response to neoadjuvant treatment compared to their counterparts of a normal weight [ 20 , 21 ] as well as worse local control following neoadjuvant treatment and surgery [ 22 ]. We sought to understand the relationship between body composition and bystander cellular response to TCM from both irradiated and mock-irradiated rectal cancer biopsies.…”
Section: Resultsmentioning
confidence: 99%